A comparison of hometown socioeconomics and demographics for black and white elite football players in the US - Allison, R.; Davis, A.; Barranco, R. (International Review for the Sociology of Sport, 2018)
Despite widespread perceptions of elite US sport as meritocratic, there is little empirical research on the social origins of those who play college and professional sports in the US or how these vary by race. We use the case of American football, linking Entertainment and Sports Programming Network`s national recruit rankings data on incoming college football players from 2007-2016 (N=929) with 2000 US Census data. Our study compares hometown socioeconomic and demographic indicators for black and white college athletes and then for those drafted into the National Football League. Findings show that the socioeconomic and demographic profiles of the hometowns producing elite football athletes vary by both athlete race and draft status. Black draftees come from denser, more socioeconomically disadvantaged and blacker hometowns than black non-drafted athletes, while white draftees come from less socioeconomically disadvantaged hometowns than white non-drafted athletes.